Comparison in the physicaland strength properties of 3 year-old Gigantochloa brang and G.Scortechinii - Razak Wahab; Mohd Tarmizi Mustafa; Mohamed Abdus Salam; Izyan Khalid; Mohd Sukhairi Mat Rasat; Irshad Ul Haq Bhat
Relationships between physical and strength properties of Gigantochloa brang and G. scortechinii were investigated. The culms of the three-year-old bamboos were selected, harvested and processed for the studies. The moisture content (MC) of the bamboo in green condition ranged between 74.54 (G. brang) and 109.18 (G. scortechinii), the MC is higher in the internodes (94.45%) than in nodes (78.61%). Position in the internal layer has MC at 125.90%, middle at 83.82% and external at 49.87%. The basic density increases from internal to external layer which started from 0.58 at inner and increased to more than 0.95 at outer part of bamboo at 12% moisture content. Shrinkage at radial, tangential and the volumetric were at 6.29%, 10.71% and 10.72 respectively for G. brang, and 8.72%, 11.74% and 16.83% for G. scortechinii. Positions having a higher rate of shrinkage were recorded on the inner (8.63, 13.50, 15.45%), follow by middle (6.85, 9.72, 12.57%) and outer (5.04, 6.52, 10.40%) respectively. The tensile strength for the bamboos ranged between 103.39 MPa (G. brang) and 122.16 MPa (G. scortechinii). The tensile strength of dried bamboo is 138.87 MPa compared with 89.95 MPa for green bamboo. The tensile of modulus of air dried bamboo is 4003.85 MPa compared with 2786.96 MPa for green bamboo. The modulus of rupture (MOR) for the bamboos ranged between 91.81-135.93 MPa. The MOR for dried bamboo was 142.21 MPa compared to the green bamboo 99.56 MPa. The modulus of elasticity (MOE) varies between 1203 MPa (nodes) to 3086 MPa (internodes) for G.scortechinii) and 3227 MPa (nodes) to 2561 MPa (internodes) for G. brang.